Linear kinematics of the underwater undulatory swimming of two backstroke starting techniques - de Jesus, Ka.; de Jesus, Ke.; Leandro Machado, R. J.; Fernandes, R. J.; Vilas-Boas, J. P. (Journal of Sports Science & Medicine, 2012)
To maximize speed while minimizing drag during the underwater phase of starts and turns, swimmers perform dolphin-like undulatory swimming. Despite the relevance to performance of the undulatory underwater swimming is extensively recognized, little is known about possible technical modifications during the undulatory cycles with specific fatigue and when performing different backstroke starts like the one with feet parallel and entirely immerged (BSFI), and the one with feet parallel and entirely above water surface (BSFE). The present study aimed to analyze the effects of the backstroke start used (BSFI and BSFE) on the kinematics of the undulated underwater swimming cycles. Simultaneously, the effect of specific fatigue due to repetition of this particular action will also be evaluated in both techniques. Methods: Four high level backstrokers (age: 22.75 ± 1.70 years, body mass: 75.95 ± 8.85 kg, height: 1.78 ± 0.06 m) performed two randomized sets of three maximal bouts of 15 m backstroke start, each set using BSFI or BSFE. A cable velocimeter (50 Hz) connected at the distal end to a harness belt attached to the swimmer`s waist was used to assess linear kinematic parameters of successive undulated underwater cycles (upward and downward kick). The kinematical analysis of the four initial and the last four undulated underwater cycles of each underwater phase was performed using a MatLab routine with a correction for the effect of cable angulation. The mean horizontal velocity and horizontal amplitude were determined in each individual velocity-time curve and presented as a mean value of each of the two groups of four undulated underwater cycles. Descriptive statistics, paired sample ttest (p < 0.05) and effect size (d) were calculated. Results: The kinematic variables were not different between BSFI and BSFE for the four initial and the last four undulated underwater cycles The four initial undulated underwater cycles showed higher mean horizontal velocity than the last four ones (p < 0.05) for BSFI (1.47 ± 0.11 vs. 1.28 ± 0.07 m/s) and BSFE (and 1.44 ± 0.04 vs. 1.30 ± 0.04 m/s), with large effect sizes (d = 0.87 and 0.83, respectively). The horizontal amplitude for the four initial undulated underwater cycles was greater than the last four in BSFI (0.61 ± 0.07 vs. 0.55 ± 0.05 m) and BSFE (0.60 ± 0.06 vs. 0.55 ± 0.07 m) with large effect sizes (d = 1.37 and 0.79, respectively). Conclusions: In terms of backstroke technique development, coaches should instruct swimmers to maintain higher horizontal velocity and amplitude of undulated underwater cycles especially at the end of this particular phase, when swimming closer to the water surface, to achieve top results.